E, S or G – What Drives Corporate Failure? - Ellis, Colin (Archives of Business Research, 2025)
Sustainability issues have become a core part of financial analysis, particularly over the past decade. While governance has always been recognized as a key factor in driving corporate performance, environmental and social issues have risen in prominence over this time. A natural question is which of these three factors has been most important in determining corporate failure in recent years. This paper uses data on corporate defaults and ESG assessments from a major credit rating agency to examine the relationship between businesses being unable to keep the financial promises and different environmental, social and governance considerations. It finds little sign of environmental risk driving defaults – so far – but both social and governance factors are statistically significant. While the relationships between ESG factors and defaults are likely to change over time, this analysis offers early insights against which those changes can be benchmarked.